James Herriot's Treasury for Children - Herriot, James (New York St. Martin's Press, 1992)
A collection of the author's stories for children, including "Mosesthe Kitten," "The Market Square Dog," and "Smudge, the Little Lost Lamb."
Keywords: Animals; Farm life